Pedekatan Holistik dalam Manajemen Kesiswaan : Akademik, Karakter, dan Bakat - Alistriana, Alistriana; Indah Suci Wulandari; Ichsandy Tanaya Abiyaksa (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Effective student management is an important part of a quality education system. This research considers a holistic approach to student management that integrates academic aspects, character development, and talent development. The aim of this study is to analyze the effectiveness of the holistic approach in enhancing academic achievement, positive character development, and student talent development. This research employs a mixed-methods approach that combines quantitative data analysis from academic results and student surveys with qualitative data from in-depth interviews with educators and field observations. Research shows that a holistic approach to student management is positively correlated with improved academic performance, stronger character, and more targeted human resource development. This result highlights the importance of integrating cognitive, affective, and psychomotor aspects into student management. The significance of this research underscores the need for a reformulation of educational policies that support the implementation of integrated student management at various levels of education.